Reproductive seasonality and early life temperature sensitivity reflect vulnerability of a seaweed undergoing range reduction - Andrews, S.; Bennett, Scott; Wernberg, T. (2014)
Temperature is a major determinant of the performance and geographical ranges of marine species. Changes in temperature can therefore result in localised mortality and shifts in species distributions, but the phenology and temperature sensitivity of many important habitatforming seaweed species has not yet been investigated. Through field observations and culture growth experiments, the present study investigated the temperature sensitivity of reproductive timing, early post-settlement growth and survival, and recruitment success of the widespread foundation seaweed Scytothalia dorycarpa in Australia. In culture, the highest settlement densities and lowest mortality rates were achieved at 15°C, and optimal temperatures for germling fertilisation occurred at 18°C, whereas temperatures greater than 20°C delayed germling settlement and significantly increased mortality rates, with no germlings surviving at temperatures greater than 23°C. Experimental findings were consistent with field observations that found adult reproductive development and gamete release to occur in synchronous pulses throughout the winter months, when seawater temperatures were ~18°C. Surveys of the latitudinal distribution of S. dorycarpa recruits showed significantly lower recruit densities in warmer, low-latitude reefs where summer maximum temperatures often exceed 23°C compared to much higher recruit densities in cooler pole-ward reefs where average summer maximum temperatures are 21 to 22°C. The timing of reproduction, latitudinal distribution of recruits and culture temperature optima all indicate high temperature sensitivity among the early life stages of S. dorycarpa. These findings help to explain the rapid range contraction of this species following a 2011 marine heatwave off the southwest coast of Australia. © Inter-Research 2014.